MAKING NEW BUSINESS MODEL FULLY FUNCTIONAL - Grublova, Eva (Doprava a spoje, 2012)
The way out from crisis disaster valley must be oriented through innovation activities that would strengthen companies' performance, their ability to hold existing core business profitable and to capture new-growth opportunities simultaneously. Today companies must transfer their prevailing business models to new ones - relying on ``shared value creation''.